THE INFLUENCE OF OWN STRESSES ON TENSILE CONCRETE STRENGTH - Fenko, O. G.; Yurko, I. A.; Karabash, L. V.; Yurko, P. A. (Academic journal Industrial Machine Building Civil Engineering, 2018)
Based on experiments results brittle duralumin samples, effect on stresses concrete (mortar) strength caused by non-uniform cross-section shrinkage (when dried) or expanding (when moistened) was inevitable. Various authors’ experiments results diversity on concrete (mortar) tensile strength of moistening and drying effect were analyzed. Reasons for increasing air-dry concrete (mortar) strength storage at beginning of humidification were explained. Wetting sample duration (intensity) effect on concrete strength was analyzed in detail and opposite results causes on concrete strength moistening (drying) effects were obtained and justified.
Keywords: own stresses; concrete strength; concrete water saturation; shrinkage; creep